The Global Gold Mining Industry: Materiality, Rent-seeking, Junior Firms and Canadian Corporate Citizenship. (1st October 2013) - Dougherty, Michael L
Abstract : The growing incidence of conflicts between multinational gold mining companies and host community residents in the developing world is contextualized by discussing the recent proliferation of small, 'junior' companies in the gold mining industry. The geological attributes of the geographical distribution of gold deposits and gold's relative scarcity allow for an industry characterized by many small and intensely competitive firms. This competition plays out as a contest for access to resource and finance rents. Firms seek resource rents by investing in lax policy environments with mineralization that favours low-cost production, and firms seek finance rents by legally incorporating in Canada where equity financing for juniors is highly subsidized and corporate governance is lenient. Integrating studies on materiality, rent-seeking and the role of government incentives provides important insights into the rise of junior gold companies and the role of these firms in mineral conflicts around the world.